THE HEROIC CHARACTER DECONSTRUCTION OF BHARATAYUDHA WAR IN MAHABHARATA EPIC - Fransiska Olivia Sipota (Universitas Aki, 2020)
The Mahabharata is an epic story written by Vyasa. The story tells about the heroism of Pandavas which ended in their victory at the battle of Bharatayudha against the Kauravas. People believes that the Pandavas are heroes who become the core of the epic story. The interpretation of heroism of Pandavas are believed by people because they are the children of God. In addition the Pandavas are believed as the protagonist characters who are powerful than ordinary human, they are good and honest. Through decnstructin theory the writer reveals the other side of the Pandavas that is hidden behind their heroic action. By reading and looking for the minor texts in the story, the writer finds that the Pandavas are not as heroic as people think. There are many things that make them look as ordinary human that are far from heroic attitude. Whereas Kauravas who are considered as the cowards and they have a bad character, but they have the attitudes as a hero more than Pandavas. The writer finds the binary oppositions in the text to search for the faults of Pandavas and the of goodness Kauravas that will change the view of the two main characters in the story. By using the theory of deconstruction the writer can find other truths in the story of the epic Mahabharata. Keywords: deconstruction analysis, hero, heroism, Derrida, Mahabharata.